Proteomic Profiling of Fast-To-Slow Muscle Transitions during Aging - Ohlendieck, Kay (Frontiers in Physiology, 2011)
Old age is associated with a large spectrum of physical ailments, including muscle wasting. Skeletal muscle degeneration drastically increases the risk of poor balance, frequent falling and impaired mobility in the elderly. In order to identify new therapeutic targets to halt or even reverse age-dependent muscle weakness and improve diagnostic methods to properly evaluate sarcopenia as a common geriatric syndrome, there is an urgent need to establish a reliable biomarker signature of muscle aging. In this respect, mass spectrometry-based proteomics has been successfully applied for studying crude extracts and subcellular fractions from aged animal and human muscle tissues to identify novel aging marker proteins. This review focuses on key physiological and metabolic aspects of sarcopenia, i.e. age-related muscle fibre transitions and metabolic shifts in aging muscle as revealed by proteomics. Over the last decade, proteomic profiling studies have clearly confirmed the idea that sarcopenia is based on a multi-factorial pathophysiology and that a glycolytic-to-oxidative shift occurs in slower-twitching senescent muscles. Both, newly identified protein factors and confirmed alterations in crucial metabolic and contractile elements can now be employed to establish a sarcopenia-specific biomarker signature.